The contribution of Imam Matrudi to the teachings of Tafsir (Journal of Philosophy Culture and Political Science, 2018)
The article considers the special contribution the well-known scholar of the author of the books “Kitabut Tauhid” and “Tauilatul Қoran” Imam Maturidi to the history of Tafsir. In order to examine in depth the principles of Imam matrudi should pay special attention to the socio-cultural and political atmosphere of the time. During that time of Imam Maturidi had different mazhabs and various progressive views on faith.At that time in order to preserve the foundations of the faith of Islam known theologian Imam Maturidi was able to give an interpretation of the Koran which reunited the mind and religious texts. This article originally referred to the occurrence and characteristics of Sunni tafsir direction, followed the principles and opinions of the Tafseer of the Quran to Imam mufassir Maturidi. As well as the conclusion of taweel and Tafseer Imam Maturidi and major contributions to the development of Maturidi to tafsir. Especially the tafsir, Tauilatul Quran, methods of interpretation of the verses and the influence of Imam Maturidi in subsequent mufassirs of Islamic world.Key words: Imam Maturidi, Quran, Tafseer, Tauilatul Қoran.